2015
DOI: 10.3109/19401736.2015.1106494
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Chrysanthemum indicum

Abstract: Chrysanthemum indicum, an important medicinal plant of Asteraceae, had a long history in use for medicine in China. In this study, the complete chloroplast genome of C. indicum was sequenced by a 454 sequencing platform, and the structure of the obtained chloroplast genome was also analyzed. The complete chloroplast genome of C. indicum was 150 972 bp in length and had a pair of inverted repeats (IR, 24 956 bp) separated by a large (LSC, 82 741 bp) and small single copy (SSC, 18 319 bp) regions. Its total GC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Phylogenetic tree revealed that A. fukudo was grouped with two Artemisia (A. montana and A. frigida), as expected. However, Guizotia abyssinica and Helianthus annuus, which belong to the subfamily Asteroideae, were placed with Lactuca sativa (Subfamily Cichorioideae) and two Cynara species (Subfamily Carduoideae), suggesting that there is still a contradiction in taxonomical classification of Asteraceae family (Xia et al 2015) (Figure 1). Figure 1.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…Phylogenetic tree revealed that A. fukudo was grouped with two Artemisia (A. montana and A. frigida), as expected. However, Guizotia abyssinica and Helianthus annuus, which belong to the subfamily Asteroideae, were placed with Lactuca sativa (Subfamily Cichorioideae) and two Cynara species (Subfamily Carduoideae), suggesting that there is still a contradiction in taxonomical classification of Asteraceae family (Xia et al 2015) (Figure 1). Figure 1.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…Common DNA barcoding sequences (ITS, matK , psbA-trnH , and rbcL ) are also not ideal for identifying Ligularia species ( He and Pan, 2015 ). Recently, researchers have screened sequences from the whole chloroplast (CP) genome from numerous plant taxa, such as Juglans L. plants and bamboo ( Zhang et al, 2011 ; Hu et al, 2016 ), or use CP genome as a super-barcode to distinguish species ( Xia et al, 2016 ). The CP genome is highly conserved in plants regardless of the size, structure, or gene content ( Tonti-Filippini et al, 2017 ), and the majority of the retained core genes are involved in the light reactions of photosynthesis or in functions related to transcription or translation ( Sato et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…By comparing with S. koriyanagi female chloroplast genome , SSC region is reversed, which is like many chloroplast genomes including Olea europaea subsp. europaea (Xia et al 2016;Chen et al 2017;Shen et al 2017;Min et al 2019) . In addition, there is no sequence variation between male and female individuals because both individuals might be originated from the same parents or parents containing same chloroplast haplotype.…”
mentioning
confidence: 99%